Distortions in the cubic primitive high-pressure phases of calcium. (21st December 2018) - Schwarz, Ulrich; Kasinathan, Deepa; Bergner, Carina; Hunger, Jens; Meier-Kircher, Katrin; Akselrud, Lev; Hanfland, Michael; Mezouar, Mohamed; Glazyrin, Konstantin; Stinton, Graham W; Husband, Rachel; Rosner, Helge; et al.
Abstract: The superconductivity in highly compressed calcium involves the occurrence of closely related low-symmetry structural patterns with an exceptionally low coordination number. Earlier theoretical and experimental results are controversial and some findings are inconsistent with our later observations in the pressure range up to 60 GPa. This situation motivated the present concerted computational and experimental re-investigation of the structural arrangement of calcium slightly above the high-pressure limit of the bcc arrangement at low-temperatures. We report here reproducible experimental evidence for a monoclinic distortion ( mC 4, space group C 2/ c ) of the calcium polymorph previously assigned to the tetragonal β -Sn structure type. In accordance, the enthalpies calculated by electronic band structure calculations show the mC 4 phase to be more stable than the undistorted β -Sn type by about 100 meV in the entire phase space. The other low-temperature phase of calcium adopts space group Cmcm ( oC 4) rather than the earlier assigned Cmmm symmetry. These structural alterations substantially effect the density of states at the Fermi level and, thus, the electronic properties.